THE EFFECT OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, AND PERCEIVED RISK ON BEHAVIORAL INTENTION OF E-WALLET USER (CASE STUDY: MANADO) - Angie Tesalonika Rewah; Maryam Mangantar; Regina Trivena Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
E-Wallet continues to develop in popularity and has attracted a lot of attention from the general public since the service it provides is valuable in terms of practicality, security, and convenience for its users while making payments. Aside from the numerous advantages that make consumers want to use E-Wallet, it turns out that a technology's level of credibility must also be a priority in the creation of its services, since this has an impact on behavioral intention of e-wallet user.The purpose of this research is to analyze The Effect of Perceived Usefulness, Perceived Ease of Use and Perceived Risk on Behavioral Intention of E-Wallet user (Case study: In Manado). This research used quantitative method. 100 samples were collected with questionnaire distributed via social medias from E-Wallet user in Manado.The result of this research shows that Perceived Usefulness (X1) Perceived Ease of Use (X2) and Perceived Risk (X3) have a positive and significant correlation with on Behavioral Intention (Y) partially and simultaneously. Multiple linear regression and 5 points Likert scale was used to help the data analysis in this research